2019
DOI: 10.5858/arpa.2018-0172-oa
|View full text |Cite
|
Sign up to set email alerts
|

The Biospecimen Preanalytical Variables Program: A Multiassay Comparison of Effects of Delay to Fixation and Fixation Duration on Nucleic Acid Quality

Abstract: Context.— Despite widespread use of formalin-fixed, paraffin-embedded (FFPE) tissue in clinical and research settings, potential effects of variable tissue processing remain largely unknown. Objective.— To elucidate molecular effects associated with clinically relevant preanalytical variability, the National Cancer Institute initiated the Biospecimen Preanalytical Variables (BPV) program. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 45 publications
1
36
1
Order By: Relevance
“…Moreover, the specific problem of FFPE material needs clarification 31 , 62 - 64 . New RNA quality metrics, which are more sensitive than the RIN values generally used up to now, are recommended to define the preanalytical RNA conditions for reliable expression analyses in future studies 63 , 64 . These are, for example, the DV 200 that represents the percentage of RNA fragments longer than 200 nucleotides or the Q-score that characterizes the ratio of the GAPDH amplicons of 165 bp to 80 bp.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the specific problem of FFPE material needs clarification 31 , 62 - 64 . New RNA quality metrics, which are more sensitive than the RIN values generally used up to now, are recommended to define the preanalytical RNA conditions for reliable expression analyses in future studies 63 , 64 . These are, for example, the DV 200 that represents the percentage of RNA fragments longer than 200 nucleotides or the Q-score that characterizes the ratio of the GAPDH amplicons of 165 bp to 80 bp.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the biomolecule class and the biospecimen type, cold ischemia times of several hours (eg, up to 4-5 hours or even longer at room temperature) have minimal or no detrimental impact on biomolecular quality, extractable quantity, or molecular test results, 14,81,83,[150][151][152] whereas other molecular analyses, sometimes for the same specimen, are altered within 60 minutes or less. ‡ Molecules may be either upregulated or downregulated, and most studies show that gene transcripts are more likely to be upregulated rather than downregulated within 2 hours of cold ischemia.…”
Section: Cold Ischemia Time: a Cold Ischemia Time Of 1 Hour Or Less Imentioning
confidence: 99%
“…80,[158][159][160][161] Current data suggest that the measurable effects of cold ischemia are, at least partially, cancer type-specific as well as biomolecule type-specific and analysis platform-dependent. 80,151 In addition, studies comparing the effects of cold ischemia on cancer tissue and normal tissue from the same organ have demonstrated that tumor tissue is more vulnerable to the effects of cold ischemia. 80,161 Since no single recommendation for cold ischemia time would be optimal for all tissues, all classes of molecules, or all analysis platforms, the recommendation put forward here represents a compromise that meets most current molecular testing needs for cancer patient specimens.…”
Section: Cold Ischemia Time: a Cold Ischemia Time Of 1 Hour Or Less Imentioning
confidence: 99%
“…There are various factors influencing the quality of biospecimens, and pre-analytical variables are crucial ( 5 , 6 ). Pre-analytical variables are divided into the pre-acquisition and post-acquisition phases.…”
Section: Introductionmentioning
confidence: 99%